A Mesh-Free Algorithm to Solve an Inverse Source Problem for Degenerate Two-Dimensional Parabolic Equation from Final Observations - Atifi, Khalid (Armenian Journal of Mathematics, 2023)
The main purpose of this work is to propose a new network architecture model for deep learning applied to solve an inverse source problem for a two-dimensional degenerate parabolic equation from final observations with degeneracy occurring anywhere in the spatial domain.